Kriteria Pembelian Motor Bekas Berdasarkan Kebutuhan Pengguna Menggunakan Metode Sugeno - Mahrizon, Dedi (LPPM UNIKA Santo Thomas Medan, 2023)
Fuzzy logic includes seven areas of artificial intelligence. Fuzzy logic is currently very developed, seen from the system used in decision making, including the purchase of used two-wheeled motorbikes. Two-wheeled vehicles are in great demand by many people, seen from the aspect of transportation, they are widely used for outside activities. The problem that often occurs to users is the lack of user knowledge in purchasing used motorbikes so that when the goods have been purchased the motorbike is damaged or difficult to purchase tools and complete documents. The purpose of this study is to assist users in making decisions in purchasing two-wheeled vehicles by taking into account predetermined criteria. In selecting criteria, there are 5 aspects that must be considered, namely, machine condition, part completeness, paperwork completeness, spare parts availability and price, output variable, namely decision. The completion method uses the AND Operator and takes the Maximum value. The final result of the defuzzification search has a value of z = 0.826 with a purchase decision.